From Microscale (400 μl) to Macroscale (425 L): Experimental Investigations of the CO2/N2‐CH4 Exchange in Gas Hydrates Simulating the Iġnik Sikumi Field Trial. Issue 5 (24th May 2018) - Schicks, J. M.; Strauch, B.; Heeschen, K. U.; Spangenberg, E.; Luzi‐Helbing, M.
Abstract: In 2012 the production of CH4 from hydrate‐bearing sediments via CO2 injection was conducted in the framework of the Iġnik Sikumi Field Trial in Alaska, USA. In order to preserve the injectivity by avoiding a formation of CO2 hydrate in the near‐well region, a mixture containing 77 mol% N2 and 23 mol% CO2 was chosen. The interpretation of the complex test results was difficult, and the nature of the interaction between the N2 ‐CO2 mixture and the initial CH4 hydrate could not be clarified. In this study we present the results of our experimental investigations simulating the Iġnik Sikumi Field Trial at different scales. We conducted (1) in situ Raman spectroscopic investigations to study the exchange process of the guest molecules in the hydrate phase on a molecular level in a flow‐through pressure cell with a volume of 0.393 ml, (2) batch experiments with pure hydrates and hydrate‐bearing sediments in pressure cells with volumes of 420 ml, and (3) the injection of a CO2 ‐N2 mixture into a hydrate‐bearing sediment in a large‐scale reservoir simulator with a total volume of 425 L. The results indicate a dissociation of the initial CH4 hydrate rather than an exchange reaction. The formation of a secondary mixed hydrate phase may occur, but this process strongly depends on the local composition of the gas phase and the pressure at given temperature. Key Points: When exposed to a CO2 ‐N2 gas mixture (23 mol%/77 mol%), no replacement of the hydrate‐bonded CH4 with CO2 or N2 could be observed Chemical environment changes due to CO2 ‐N2 injection led to two processes: dissociation of initial hydrate and formation of a mixed hydrate The dissociation of the CH4 hydrate occurs at pressures within the CH4 hydrate stability field and increases with decreasing pressure